2020
DOI: 10.1108/jkm-01-2020-0018
|View full text |Cite
|
Sign up to set email alerts
|

Mobile technology to give a resource-based knowledge management advantage to community health nurses in an emerging economies context

Abstract: Purpose Knowledge is a key success factor in achieving competitive advantage. The purpose of this paper is to examine how mobile health technology facilitates knowledge management (KM) practices to enhance a public health service in an emerging economies context. Specifically, the acceptance of a knowledge-resource application by community health workers (CHWs) to deliver breast cancer health care in India, where resources are depleted, is explored. Design/methodology/approach Fieldwork activity conducted 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 70 publications
(119 reference statements)
1
24
0
Order By: Relevance
“…Similarly, Hampshire et al (2017) used qualitative approach to examine health-workers’ mobile phone practices and associated political-moral economies of care in Ghana and Malawi. In addition, Fletcher-Brown et al (2020) used this approach to examine the acceptance of a knowledge-resource application by community health workers (CHWs) to deliver breast cancer healthcare in India. In our study, nine (9) FGDs, three (3) in each region, were conducted with CHNs, reflecting the different experiences in urban, peri -urban and rural areas across the regions.…”
Section: Study Methodsmentioning
confidence: 99%
“…Similarly, Hampshire et al (2017) used qualitative approach to examine health-workers’ mobile phone practices and associated political-moral economies of care in Ghana and Malawi. In addition, Fletcher-Brown et al (2020) used this approach to examine the acceptance of a knowledge-resource application by community health workers (CHWs) to deliver breast cancer healthcare in India. In our study, nine (9) FGDs, three (3) in each region, were conducted with CHNs, reflecting the different experiences in urban, peri -urban and rural areas across the regions.…”
Section: Study Methodsmentioning
confidence: 99%
“…Out of the six empirical papers, four papers focus on the issues related to KM at an individual level, one at the organizational level and one at the intersection of organization and community. Among those at an individual level, the Fletcher-Brown et al (2021) paper focuses on the frontline health workers in an Indian context. The Turulja et al (2021) paper focuses on health-care providers at the primary health care centers in Bosnia and Herzegovina.…”
Section: Evaluating and Investigating Knowledge Management Practices And Ict In Health Care: An Emerging Economies Perspectivementioning
confidence: 99%
“…Depiction of diverse aspects of KM in the health-care domain types of technologiesm-Health, Web 2.0, messaging and text mining. The papers also include a range of different methodologies applied, from qualitative(Fletcher-Brown et al, 2021;Tripathi et al, 2021: Turulja et al, 2021 to quantitative…”
mentioning
confidence: 99%
“…In fact, the adoption of digital technologies can improve the performance of main health-care business processes and increase efficiency by allowing the delivery of better quality and reduced response times (Laurenza et al , 2018). A recent study with frontline community health workers in India (Fletcher-Brown et al , 2020) found that KM plays a facilitating role in mobile-health in an emerging economies context. KM is also found to have a decisive role in IoT-driven mobile-health, helping health organizations to identify business requirements and address privacy and security issues (Lokshina and Lanting, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%